Urban Problems, the impact on future cities -A concept for Baghdad future sustainable development- - سهاد كاظم عبد الموسوي (Wasit Journal of Engineering Sciences)
Urban problems affects both Developed and Third World, the problems include necessity for land, energy consumption and urban waste, these problems affect the environment and ecology system and decrease the quality of healthy inhabitants living and there is a lack in sustainable treatment for these problems, the research hypothesize that sustainable urban development can be achieved if urban planning consider an effective transport system and infra structure with the support of land use administrational tools, the research aims to define future sustainable urban development schemes with a future description for sustainable Baghdad urban future, the research defines urban problems and the available treatments to outline the meaning of sustainable urbanism.